2005
DOI: 10.1007/s11010-005-3077-1
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CK2 induces apoptosis in cancer cells – A potential approach to cancer therapy

Abstract: We have previously documented that naked antisense CK2alpha ODN can potently induce apoptosis in cancer cells in culture and in mouse xenograft human prostate cancer. The effects of the antisense CK2alpha are related to downregulation of CK2alpha message and rapid loss of the CK2 from the nuclear compartment. Here we demonstrate that downregulation of CK2 elicited by diverse methods leads to inhibition of cell growth and induction of apoptosis. The various approaches to downregulation of CK2 employed were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 22 publications
10
101
0
Order By: Relevance
“…As discussed above, a significance of these observations is that since CK2 downregulation by various means causes cell death, this approach has the potential of leading to novel strategies for cancer therapy. Studies in our laboratory are in progress along these line Slaton et al, 2004;Ahmad et al, 2005;Wang et al, 2005b;Wang et al, 2006b). …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As discussed above, a significance of these observations is that since CK2 downregulation by various means causes cell death, this approach has the potential of leading to novel strategies for cancer therapy. Studies in our laboratory are in progress along these line Slaton et al, 2004;Ahmad et al, 2005;Wang et al, 2005b;Wang et al, 2006b). …”
Section: Discussionmentioning
confidence: 91%
“…The induction of apoptosis was apparent when CK2 activity was reduced by 30-40% in the nuclear compartment (chromatin or nuclear matrix) Wang et al, 2001). Recent studies by us (Wang et al, 2005b;Wang et al, 2006a;Ahmad et al, 2006;Ahmad et al, 2007) and by others (Ruzzene et al, 2002;Seeber et al, 2005;Pagano et al, 2007;Mishra et al, 2007;Hamacher et al, 2007) have also shown that chemical inhibitors of CK2 are effective in inducing cell death, and that induction of death by chemical agents is blocked by forced overexpression of CK2 (Wang et al, 2006a). Delivery of antisense CK2α into a xenograft prostate cancer in the mouse also demonstrated potent induction of apoptosis associated with significant reduction of the CK2 signal in the nuclear matrix .…”
Section: Ck2 and Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of this component would improve our understanding of the complex regulatory network governed by activity of CK2 kinase. The other issue is linked with the potential use of inhibitors of CK2 in anticancer therapy (20,21) and concerns their efficacy as sensitizers to anticancer agents such as TRAIL. Although the schedule in which TBB treatment precedes administration of sTRAIL does not cause more cell death, it prevents elevated metabolic activity of the cancer cell that may overwhelm the apoptotic efficacy of the combination of TBB and TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…It also promotes cell survival acting on c-FLIP expression (16), increasing the level of survivin (17), and enhancing degradation of tumor suppressors: PML (18) and inositol hexakisphosphate kinase-2 (19). Due to general pro-survival effects of CK2 activity, its inhibitors are seriously considered as potential anticancer drugs (20,21). Their application seems especially promising in combination with other anticancer agents whose effective concentration might be reduced this way.…”
Section: Introductionmentioning
confidence: 99%